2008
DOI: 10.1038/pcan.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and free oestradiol are independent risk factors for benign prostatic hyperplasia

Abstract: The aetiology of benign prostatic hyperplasia (BPH) remains unclear. The objective of the present study was to test the insulin, oestradiol and metabolic syndrome hypotheses as promoters of BPH. The design was a risk factor analysis of BPH in which the total prostate gland volume was related to endocrine and anthropometric factors. The participants studied were 184 representative men, aged 72-76 years, residing in Gö teborg, Sweden. Using a multivariate analysis, BPH as measured by the total prostate gland vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 41 publications
7
46
0
2
Order By: Relevance
“…[18][19][20] Moreover, elevated insulin levels are also linked with BPH, another prostate-related disease. 21 Among men with PC, those with C-peptide concentrations (a marker of insulin) in the highest quartile had a 2.4-fold increased PC death vs men in the lowest quartile. 22 Whether the energy surplus from weight gain, independent of obesity, produces the same microenvironment as obesity is unknown and further investigation is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…[18][19][20] Moreover, elevated insulin levels are also linked with BPH, another prostate-related disease. 21 Among men with PC, those with C-peptide concentrations (a marker of insulin) in the highest quartile had a 2.4-fold increased PC death vs men in the lowest quartile. 22 Whether the energy surplus from weight gain, independent of obesity, produces the same microenvironment as obesity is unknown and further investigation is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…The minor alleles of these SNPs were associated with an increased risk of BPH. Previous studies have shown that the serum estrogen level is associated with prostate volume and other characteristics of BPH (22,23). Although the exact role of ESR2 in the mechanism of BPH has not yet been fully determined, it is suggested that ESR2 located in epithelial cells inhibits the proliferation of the prostate and activates apoptosis in BPH (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data [27,28] have, in fact, suggested that low testosterone might be an additional MetS component that induces urinary tract disease. One investigation [29] indicated that BPH and the components of MetS shared the same endocrine aberration, which included an increased level of free estradiol, and also showed that a reduced testosterone level was not linked to the same endocrine aberration in the two diseases. However, our findings suggested there was no significant difference in the testosterone or androgen levels between the two groups.…”
Section: Discussionmentioning
confidence: 99%